Preparing improvement teams to manage complex change in a continuous improvement program - Anderson, Erin (Frontiers in Education, 2025)
This study is a cross-case comparison of three cohorts of teams of educators implementing a continuous improvement program in partnership between a university and a district. Using interviews, document analysis, and observation, the researchers looked within and across cohorts to determine how the teams applied the continuous improvement process to their work. Using a complex systems change framework, this study explored the relationship between the program structure and content and the implementation of an improvement process at the schools, including the challenges and benefits of applying the process. By providing the components to manage complex change, this program was able to help schools report benefits of (a) deliberate, deep, and intentional change, (b) within school and across school learning and collaboration, (c) shifting mental models and mindsets, and (d) greater collective responsibility for improvement by mitigating the challenges of (a) the tension between the time available and the complexity of the process, (b) the alignment between the process and district priorities resulting in competing priorities, and (c) the capability to spread the learning school-wide.